Force/Position Hybrid Control for Cable-driven Parallel Robots Based on the System Stiffness - Chen Keju; Zhang Shangying; Zhang Jilei; Luo Shiyang; Zhang Bowei (Jixie chuandong)
The supporting stiffness analysis of the eight-cable 6-DOF cable-driven parallel robot is conducted, and the force/position hybrid control is carried out on this basis. Firstly, the cable-driven parallel robot is described systematically. Secondly, a kinematic analysis is conducted according to the principle of vector closure. The force of the mobile platform is analysed, and the static equilibrium equation is derived by Newtonian mechanics. After that, the relationship between the load change and the position change is described by the stiffness matrix in the operational space, the analytical expression of the supporting stiffness is deduced, and the influencing factors of supporting stiffness are analysed. Moreover, the factors of system stiffness, mobile platform posture accuracy and force control stability are considered, integrating the force/position hybrid controller. The simulation results show that the position error of the mobile platform is effectively reduced by the force/position hybrid control strategy, which is designed based on the stiffness analysis. Finally, the accuracy and effectiveness of the stiffness model and the force/position hybrid control strategy are verified by experiments.